Assessing the Determinants and Prospects for the Pace of Market Access by Countries Emerging from Crisis : Further Considerations. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This paper essentially confirms the main findings of the paper previously discussed by the Board. It (i) discusses the external conditions and the domestic economic policy stance needed for a country to reaccess international Capital markets and (2) describes other considerations to reaccess markets, including a communications strategy and the design of debt instruments to regain market access.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet